PWE-257 Establishing a tertiary referral service for patients with locally advanced and recurrent rectal cancer. (22nd June 2015) - Karim, A; Cubas, V; Ibrahim, H; Goldstein, M; Bowley, D; McArthur, D
Abstract : Introduction: The management of patients with locally advanced rectal cancer (LARC) and recurrent rectal cancer (RRC) (collectively referred to as Beyond TME rectal cancer) presents particular surgical challenges. It has been shown that, in carefully selected patients in centres specialising in their treatment, surgical resection can result in good outcomes. We present results from our unit, establishing a tertiary referral centre for LARC and RRC in the West Midlands, UK. The team, set up after a number of its members had worked in other high volume units, comprises specialist colorectal surgeons, radiologists, pathologists, urologists, oncologists and full MDT staff. Referrals are received through the MDT from other units within the West Midlands. Method: A prospective database was set up to collect data on all referrals received for LARC and RRC. Demographic, radiological and histological data was recorded. Length of stay, short and medium term morbidity, and long-term outcome, including recurrence, were all analysed. Results: A total of 34 referrals were received from October 2011 to December 2014. 7 patients were declined surgery based upon anatomical factors (e.g. extensive pelvic sidewall involvement), whilst 25 patients went on to have surgery (2 further patients' surgery pending). Of those operated, M: F ratio 19:6 and median age was 60 years old. Surgery was for LARC (n = 11) and RRC (14). Surgery involved multi-visceral resection, according to the anatomical distribution of disease. Histology results for resection margins showed R0=19, R1=5, and R2=1. Median length of stay was 11 days. Median follow up was 12 months with 5 patients found to have further recurrence (2 R1 and 3 R0). Post-op complications were limited to 2 patients with wound infections managed with dressings, and one patient who developed hospital acquired pneumonia. One patient required nephrostomy in the post op period for ureteric stenosis on the contralateral side to a re-implanted ureter. 4 patients died within the follow up period and were all known to have recurrence. Conclusion: Our initial results have shown acceptable outcomes for patients in terms of short-term morbidity and recurrence when compared to more established centres. The management of patients with LARC and RRC involves complex decision-making processes and challenging surgery. We believe this requires specialist input. As such, establishing a specialist referral unit for these cases is achievable and important in improving outcomes for this group of patients. Disclosure of interest: None Declared.